PENGARUH PENDAPATAN DAN KONSUMSI RUMAH TANGGA TERHADAP KESEJAHTERAAN KELUARGA PETANI DI DESA JANJA KOMPI KECAMATAN LAMPASIO KABUPATEN TOLITOLI: Studi Kasus Desa Janja Kompi Kecamatan Lampasio Kabupaten Tolitoli - Ramlawati Ramlawati; Hilmi Hilmi (Jurnal Riset Ilmu Ekonomi, 2023)
This study aims to determine how the influence of household income and consumption variables on the welfare of Farmer Families in Janja Company Village, Lampasio District, Tolitoli Regency. This study used associative quantitative methods. Data sources are primary data obtained through questionnaires, observations, interviews and documentation related to this study. Based on the results of regression data, the study can be partially concluded that income variables have a significant effect on the welfare of farmer families. While the variable of household consumption does not have a significant effect. In addition, the results of data processing show a significant influence of household income and consumption simultaneously on household welfare.